(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
In present era, attentively engaged in professional and social life, eventually forgotten normal sit and lie postures. Hustles like Jerky movements during travelling, poor postures, bending and lifting awkward etc., creates extreme pressure on the spine which affects functional ability of lower limbs. Hence Gridhrasi is taken for present clinical study and is approximately correlated to sciatica. Sciatica is a set of symptoms including pain that may be caused by general compression or irritation of one of five nerve roots that give rise to the sciatic nerve. This can also happen by compression or irritation of the sciatic nerve itself. The pain is felt in the lower back, buttock, thigh, leg and foot. Basti karma is praised by all the Acharyas in the management of Gridhrasi to relive from the pain, to improve functional disability and restore functional abilities & controls the condition. The study was conducted with the aim of comparing Ashtakatwaratailamatrabasti with Sahacharatailamatrabasti in the management of Gridhrasi. The clinical trial included 40 patients of Gridhrasi categorized into two groups. 20 patients recieved 75 ml of Sahachara Taila Matrabasti and 20 patients recieved 75 ml of Ashtakatwara Taila Matrabastiafter sthanika abhyanga and swedana for 7 days. Both the groups are having similar effect on reducing the symptoms statistically. Among the subjective and objective parameters B group (Ashtakatwara taila matrabasti) showed better reduction% in Ruk, Sthambha, Toda, right lateral flexion, left lateral flexion and extension of lumbar movement, walking time, VAS, Oswesry disability index.